Universidade de classe mundial no brasil: trabalho, regulação e subordinação à economia política do Banco Mundial - Fargoni, Everton Henrique Eleutério (2025)
This thesis investigates, from the perspective of political economy and the historical-dialectical method, the influence of the World Bank (WB) on the regulatory policies of Brazilian public higher education, focusing on the dissemination of the World-Class Universities (WCU) model. The study is based on the premise that the consolidation of this international paradigm does not arise from voluntary adaptations or isolated administrative choices, but rather emerges from a complex process forged by transnational power networks and mediated by technical, symbolic, and financial devices that permeate the institutional fabric of Brazilian universities. Centering the analysis on academic labor, regulation, and subordination, the research critically articulates the historical trajectory of the WB, the reconfiguration of the social role of the public university, and the rise of a rationality oriented toward excellence, competitiveness, and integration into global evaluation circuits. The investigation draws on a corpus composed of eight paradigmatic WB reports, national higher education legislation, and guiding documents, analyzed through concepts such as totality, historicity, contradiction, mediation, hegemony, and alienation, engaging throughout the text with classic and contemporary authors of international reference. The analysis shows that the adoption of the WCU model introduced heteronomous forms of regulation, reorganizing not only curricular structures and university management, but also research, teaching practices, and academic labor relations, fostering the centralization of decision-making power, institutional standardization, and the commodification of knowledge. The study demonstrates that the influence of the WB materializes as a vector of structural reconfiguration, never reducible to a merely technical or disinterested act; on the contrary, it shapes an architecture of subordination in which the Brazilian public university is called to serve the interests of global financial capital, often to the detriment of social demands and national development projects. Pressures for internationalization, rankings, technological innovation, and corporate partnerships turn the university into a showcase of results and a laboratory of institutional adaptation, eroding its critical social function and autonomy. The research reveals that such transformations do not occur through direct imposition, but through symbolic, technical, and political mechanisms that permeate institutional and everyday practices, altering meanings, priorities, and actions. Ultimately, the thesis answers the central question affirmatively, demonstrating that the World Bank exerts decisive, multifaceted, and often covert influence over the transformation of Brazilian public universities into world-class institutions, with profound repercussions for academic labor, citizenship formation, the social role of the university, and the future of national public higher education.